2005
DOI: 10.1074/jbc.m500963200
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor and Hypoxia-induced Expression of CXC Chemokine Receptor 4 on Non-small Cell Lung Cancer Cells Is Regulated by the Phosphatidylinositol 3-Kinase/PTEN/AKT/Mammalian Target of Rapamycin Signaling Pathway and Activation of Hypoxia Inducible Factor-1α

Abstract: Non-small cell lung cancer (NSCLC) expresses a particularly aggressive metastatic phenotype, and patients with this disease have a poor prognosis. CXC chemokine receptor 4 (CXCR4) is a cell surface receptor that has been shown to mediate the metastasis of many solid tumors including lung, breast, kidney, and prostate. In addition, overexpression of the epidermal growth factor receptor (EGFR) is associated with the majority of NSCLC and has been implicated in the process of malignant transformation by promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
261
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(278 citation statements)
references
References 41 publications
(84 reference statements)
17
261
0
Order By: Relevance
“…Although EGFR was suggested to be one of upstream regulators of PDK-1/AKT and Stat3 pathways (Engelman et al, 2005;Ivanov and Hei, 2005;Phillips et al, 2005), the role of EGFR activation plays in relation to PDK-1/AKT/mTOR/p70S6K/S6 cascade in breast cancers has not been firmly established. In this study, we have shown that moderate to high levels of EGFR phosphorylation (Y1086) were observed in 67 out of 89 (75.3%) primary breast tumours and was associated with invasive breast tumours (Po0.05) (Table 1).…”
Section: Phosphorylated Egfr(y1068) Was Exclusively In the Nucleus Ofmentioning
confidence: 99%
“…Although EGFR was suggested to be one of upstream regulators of PDK-1/AKT and Stat3 pathways (Engelman et al, 2005;Ivanov and Hei, 2005;Phillips et al, 2005), the role of EGFR activation plays in relation to PDK-1/AKT/mTOR/p70S6K/S6 cascade in breast cancers has not been firmly established. In this study, we have shown that moderate to high levels of EGFR phosphorylation (Y1086) were observed in 67 out of 89 (75.3%) primary breast tumours and was associated with invasive breast tumours (Po0.05) (Table 1).…”
Section: Phosphorylated Egfr(y1068) Was Exclusively In the Nucleus Ofmentioning
confidence: 99%
“…[6][7][8][9] Hypoxia association with treatment failure is exhibited as resistance to radiotherapy and chemotherapy and the presence of quiescent hypoxic cells resistant to anti-proliferative therapy. 5 The contribution of hypoxia to a more aggressive, invasive, and metastatic phenotype involves multiple mechanisms, including: promotion of genetic 10 and epigenetic changes; 11 inhibition of apoptosis; 12 a shift to glycolytic metabolism; 13 up-regulation of survival factors; 14 production of enzymes mediating invasiveness; 15 stimulation of angiogenic signals; 15 induction of epithelial to mesenchymal transition (EMT); 16 and preferential location of cancer stem cells to hypoxic subregions. 17 TH-302 (1-Methyl-2-nitro-1H-imidazol-5-yl)methyl N,N 0 -bis(2-bromoethyl)phosphorodiamidate) is a hypoxia-activated prodrug composed of 2-nitroimidazole linked to a brominated analog of isophosphoramide mustard (Br-IPM).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia-inducible factor 1 is degraded through ubiquitylation involving the von Hippel -Lindau tumour-suppressor protein, whose loss of function, detected in renal cancer and neuroendocrine tumours, impairs HIF-1a degradation and favours the stimulation of mTOR signalling (Melillo, 2007). Finally, it has been reported that HER2 activation in normoxic cells increases HIF-1a via PI3K, Akt and mTOR (Laughner et al, 2001), and that EGF induces HIF-1a, which can be prevented by using mTOR inhibitors under both normoxic and hypoxic conditions (Phillips et al, 2005). Taken together, these studies demonstrate that mTOR is a positive regulator of HIF-1a translation and an inducer of HIF-1/VEGFdependent angiogenesis.…”
mentioning
confidence: 99%